(untitled) (Acta Scientiarum. Health Sciences, 2025)
Ä°ncrease and implementation of training programs in order to recognize the risk factors of breast cancer,in women, at an early stage and to increase their awareness of their own bodies are very important. The aim of the present research was to detect the effect of self-breast examination provided to women between 18 and 49 years of age and practice on the belief of women on their breast health. The research is a randomized controlled interventional design including a pre-test and post-test. The universe of the research consisted of the female parents of the students studying in two schools where the research was conducted. The research sample consisted of 98 women, 45 in the intervention group and 53 in the control group, selected by simple random sampling. It was detected that the perception of disability increased from 14.86 ± 3.53 to 16.51 ± 2.62, and the sense of confidence increased from 24.35 ± 5.41 to 31.20 ± 4.86 in the intervention group after the training (p<0.01).It was detected at the end of the study that women had a positive attitude towards the practices to prevent breast cancer after the training. It was detected that there was a significant decrease in the level of barriers perceived by women to take protective measures. Nurses gain basic knowledge and skills BSE practice to be a role model for other women in the society, and organize appropriate training programs in order to encourage BSE awareness and practices.